Oral malignant lesions in a sample of patients in the north of Iraq (Retrospective study) - Ali I Al-Niaimi (University of Mosul, College of Dentistry, 2006)
Aim: To determine the frequency of occurrence and the distribution of different oral malignant lesions in a sample of patients in the north of Iraq. Materials and Methods: This study including the review of 6603 patients' files with different types of malignant tumors of the body between the years 1995- 1999 and the cases affecting the oral cavity were isolated and undergo descriptive statistical analysis. Results: From the 6603 patients' files reviewed, only 119 cases (2%) had malignant lesions of the oral cavity with age range between 2.5-90 years and the mean of age was 58.3 years. Male:female ratio was 1.2:1. Squamous cell carcinoma was the predominant tumor of the oral cavity. Lower lip was the most commonly affected site by the oral cancer. Conclusion: Oral cancer included many types of tumors but the predominant type is the squamous cell carcinoma that takes many forms. Although it show high occurrence over the age of 40 years but it may occur at any age and sex. The other types of cancer although they are rare in the oral cavity but they should be taken in consideration during diagnosis of oral cancer.